Pelatihan dan Pendampingan Teknik Sampling dalam Penelitian Skripsi Mahasiswa FE Universitas Almuslim - Yusuf, Musrizal; Mukhlis, Mukhlis; Afriana, Afriana; Bahri, Saiful (Aceh Journal of Community Engagement (AJCE), 2024)
The community service carried out by the Almuslim University lecturer team has contributed to improving the quality and competence of students, especially in sample research, sampling steps and determining sample size. The aim of providing community service is to provide knowledge about the concept of sample research and methods for determining samples and sample size through training and mentoring activities. The hope is that participants (students) can complete their thesis on time. This training, which also provides direct assistance, helps participants apply concepts/material to each participant's case so as to produce significant findings in accordance with scientific viewpoints and expectations. The training and mentoring stages end with an evaluation of the results. The results are described as improving participants' understanding and skills by providing a positive learning experience for participants